MASC: a museum in search of identity - OLIVEIRA, Sandra Regina Ramalho e (2007)
The present article presents relevant aspects of the Art Museum of Santa Catarina – MASC, aiming to offer reflections not only for professionals of this area, but also for people involved in the existence and purposes of this Institution, who are or should be all citizens from the State of Santa Catarina, since it is a state-owned. The museum was founded in 1948 and called the Museum of Modern Art of Florianopolis, and in little more than a half-century its name was changed and its location was moved five times, and since then, it has sailed according to the winds or the calm determined by the changes in public policy. At times it only did not sink due to the efforts of idealists interested in it, as in the movement that culminated in its origin. Nowadays (2010), while its physical structure is being renovated, the administration works toward a re-organization, where the definition of a well-delineated identity could be included.